2017
DOI: 10.3855/jidc.8579
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Escherichia coli pathovars of phylogroups B2 and D isolated from animals in Tunisia

Abstract: Introduction: The virulent Escherichia coli strains responsible for extraintestinal infections were mainly belonged to B2 and D phylogroups. However, no past studies have determinate via the presence of virulence genes the frequency of E. coli pathovars recovered from animals housed in farms in Tunisia. The aims of this study were to investigate 26 E. coli isolated from healthy and diarrheic animals and to determinate via the presence of virulence genes the frequency of pathovars. Methodology: Twenty-six E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
0
1
1
Order By: Relevance
“…Phylogroups A and D were detected in approximately 27% of the animals. These two phylogroups are more common in humans (BAILEY et al, 2010) and have been reported at lower frequencies in some animal species than those found in this study (KILANI et al, 2017;XAVIER et al, 2022). This detection raises two hypotheses: either isolates from phylogroups A and D are part of the microbiota of these animals, unlike some wild species already studied (CRISTÓVÃO et al, 2017;ZURFLUH et al, 2019), or there is external influence, such as contamination of riverbeds by human and domestic animal waste or transmission by contaminated feed (AMARSY et al, 2019;GUENTHER et al, 2011;KARAKAYA et al, 2022).…”
Section: Speciescontrasting
confidence: 42%
“…Phylogroups A and D were detected in approximately 27% of the animals. These two phylogroups are more common in humans (BAILEY et al, 2010) and have been reported at lower frequencies in some animal species than those found in this study (KILANI et al, 2017;XAVIER et al, 2022). This detection raises two hypotheses: either isolates from phylogroups A and D are part of the microbiota of these animals, unlike some wild species already studied (CRISTÓVÃO et al, 2017;ZURFLUH et al, 2019), or there is external influence, such as contamination of riverbeds by human and domestic animal waste or transmission by contaminated feed (AMARSY et al, 2019;GUENTHER et al, 2011;KARAKAYA et al, 2022).…”
Section: Speciescontrasting
confidence: 42%
“…The frequency of phylogroups is lower (Carlos et al 2010;Jakobsen et al 2010). However, based on several studies, based on the presence of several virulence genes, B 2 and D phylogroups strains appear to be more toxic (Kilani et al 2017). Interestingly, no significant relationship was found between antibiotic resistance and the members of the phylogenetic group of the isolates.…”
Section: Discussionmentioning
confidence: 91%